Tradition’s Vital Role: Exploring the Multifaceted Functions of Mandi Ka Luak in Minangkabau Society - Utami, Viviana; Ahmad, Sulthan; Wahyuni, Dwi (UIN Sunan Gunung Djati Bandung, 2023)
Traditions play a significant role in preserving the identity and values of a society. One such tradition that has been passed down through generations is the Mandi Ka Luak tradition in Nagari Sungai Antuan. This research aims to trace the symbolic meanings embedded in the Mandi Ka Luak tradition and understand the functions associated with it. A qualitative research method was employed with a case study approach. Data were collected through in-depth interviews with traditional leaders, religious figures, and community leaders, as well as document analysis. The findings reveal that the Mandi Ka Luak tradition holds symbolic meanings within elements such as the seven-colored thread bracelet, baby’s hair-cutting ceremony, symbolic feeding, the use of coconut shells, and communal feasting. Furthermore, the tradition continues to be practiced because it plays a crucial role in fulfilling various basic needs of the community. It meets the needs for security and growth by eliminating taboos and superstitions, providing recreation, and strengthening social bonds through family and community ties. Additionally, Mandi Ka Luak contributes to the preservation of cultural identity as part of the ancestral heritage carefully upheld by the community. This research provides a deeper understanding of the continuity of the Mandi Ka Luak tradition within the context of Nagari Sungai Antuan and raises questions about the role of culture in an ever-changing modern society.